Produção de bioetanol e biometano a partir da biomassa de spirulina sp. - Rempel, Alan (2018)
The high demand for renewable and more sustainable sources of fuel that can replace the current energy matrix based on oil has led to the search for new sources of biomass, among which the algal biomass stands out. Microalgae have advantages over other raw materials because they do not need arable land for their cultivation, not competing with food production, besides helping to fix atmospheric carbon dioxide. The production of bioethanol from microalgal biomass has been reported, but the efficiency of this production process is still low, and there is a need for optimization of the production stages and cost reduction, which can be accomplished through the study of pre-treatments biomass and immobilization of enzymes used in hydrolysis, as well as the use of residues generated to obtain other biofuels, such as biomethane, contributing to increase the economic viability of the process as a whole. The objective was to produce bioethanol from Spirulina sp. LEB 52 and to use waste from the production of bioethanol in the production of biomethane. The microalga was cultivated in open tanks of 10 L using Zarrouk 20% medium, obtaining a biomass with 55% of carbohydrates, which was submitted to different pre-treatments for cellular rupture by physical methods, aiming to study which would be the most efficient in the release of intracellular polysaccharides. Afterwards, they were hydrolyzed by commercial amylolytic enzymes (alpha-amylase and amyloglucosidase), which were previously characterized for optimum ranges of pH and temperature of action. The hydrolysis of the algal biomass was carried out after pretreatment, using liquid enzymatic extracts and immobilized in polyurethane. The enzymes were immobilized separately and joined together in the support. Afterwards, enzymatic saccharification tests were performed using the free enzymes, with subsequent alcoholic fermentation. In alcoholic fermentation, the initial concentration of reducing sugars in the must and the supplementation of the hydrolyzate with nutrients were studied. The residues from saccharification and the fermentation process were subsequently used for the generation of biomethane. The best pre-treatment for cell disruption was freezing / thawing. In the characterization of the enzymes for optimum pH and temperature, both enzymes had the best results at 50 ºC and pH 5.5. With the non-immobilized enzymes results of near-100% biomass hydrolysis efficiency were obtained using 1% (v/v) of each of the enzymes. With the immobilized biocatalysts, the hydrolysis efficiencies were 83% using 1% (m/v) support containing the immobilized enzymes together. The fermentations presented efficiencies of bioethanol production around 83% without addition of nutrients to the must and with less hydrolyzate addition in the preparation of the inoculum, obtaining 23 g / L of ethanol. Ethanol production residues had a high bioethanol production potential of about 422 LN (kgSVad-1). Thus, it is possible to make use of these residues, thus giving more profitability and viability in the production process, thus providing a cycle closure, from microalgae cultivation to bioethanol production and ending with the use of residues in production of biomethane, thus adding greater viability and sustainability to the process.